Conversion of light-energy into molecular strain in the photocycle of the photoactive yellow protein. Issue 4 (4th January 2016) - Gamiz-Hernandez, Ana P.; Kaila, Ville R. I.
Abstract : The Photoactive Yellow Protein (PYP) converts light energy into molecular strain, stored in the early pR0 -photocycle intermediate. Abstract : The Photoactive Yellow Protein (PYP) is a light-driven photoreceptor, responsible for the phototaxis of halophilic bacteria. Recently, a new short-lived intermediate (pR0 ) was characterized in the PYP photocycle using combined time-resolved X-ray crystallography and density functional theory calculations. The pR0 species was identified as a highly contorted cis -intermediate, which is stabilized by hydrogen bonds with protein residues. Here we show by hybrid quantum mechanics/classical mechanics (QM/MM) molecular dynamics simulations, and first-principles calculations of optical properties, that the optical shifts in the early steps of the PYP photocycle originate from the conversion of light energy into molecular strain, stored in the pR0 state, and its relaxation in subsequent reaction steps. Our calculations quantitatively reproduce experimental data, which enables us to identify molecular origins of the optical shifts. Our combined approach suggests that the short-lived pR0 intermediate stores ∼1/3 of the photon energy as molecular strain, thus providing the thermodynamic driving force for later conformational changes in the protein.